Service Location Protocols for mobile wireless ad hoc networks. (18th June 2007) - Toh, C.K.; Guichal, Guillermo; Kim, Dongkyun; Li, Victor O.K.
As service-oriented networks are essential in our lives, service location, access and location provisioning over wired and wireless networks will govern users' satisfaction. We, therefore, present several approaches to service location in ad hoc networks: distributed broadcast query; query via service co-ordinators (SC); a hybrid combination. We also evaluated these approaches in terms of service availability (SA) and control overhead under variable network sizes and mobility scenarios. Simulation results showed that the distributed query approach suffered from high control overhead. The SC based approach provides a more scalable architecture by providing different service areas. Finally, the hybrid approach provided greater flexibility and robustness.